Biogenesis and Function of Transfer RNA-Related Fragments (tRFs). Issue 8 (August 2016) - Kumar, Pankaj; Kuscu, Canan; Dutta, Anindya
Abstract : Noncoding small RNAs arise from the various un-annotated and annotated regions of the genome. When they arise from annotated genes, the noncoding small RNAs are functionally different from the parent genes. This is a brief review of one class of noncoding small RNAs, tRNA-related fragments (tRFs), which are generated from tRNA. tRFs have been suggested to have roles in cell proliferation, priming of viral reverse transcriptases, regulation of gene expression, RNA processing, modulation of the DNA damage response, tumor suppression, and neurodegeneration. Trends: High-throughput sequencing resulted in the discovery of a new class of small RNAs: tRFs and stress-induced tRNA halves (tiRs). tiRs are activated under stress conditions and modulate the stress response. tRFs are heterogeneous class of small RNAs, with the most abundant classified into several groups: tRF-5, tRF-3, tRF-1, tiRs, and tRF-2. The first three are currently in the tRF database. Many tRFs have distinct biological functions as tumor suppressors, oncogenes, or regulators of protein synthesis, apoptosis, or neurodegeneration. Two recent studies identified tRNA fragments in sperm that alter gene expression in the embryo depending on the paternal diet. Thus, tRFs generated during spermatogenesis can act as signaling molecules in the embryo and regulate gene expression in the next generation.